THE CONCEPT OF PRENATAL EDUCATION IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Fatimah, Fatimah; M. Farhan Arib; Suryana, Ermis; Karolina, Asri (Conciencia, 2024)
This study discusses the concept of prenatal education from the perspective of Islamic education. Prenatal education is an early stage of education that begins during pregnancy, which has an important role in shaping the character and personality of children. From the perspective of Islamic education, prenatal education is considered an important foundation for the spiritual, moral, and intellectual development of children. Islam teaches that attention to children's education begins in the womb, through the behaviour, prayers, and practices of parents, especially mothers. The research method used is a literature review by analysing various literature related to prenatal education and Islamic education. The results of the study show that prenatal education in Islam involves various aspects such as the physical and mental health of the mother, reading the Qur'an, prayers, and an environment that supports positive fetal development. Good prenatal education is expected to produce a generation that is noble, intelligent, and faithful.